PERANCANGAN VIDEO FEATURE DOKUMENTER INDUSTRI TAMBANG BATU KAPUR BUKIT TUI PADANG PANJANG - HAVIZ EMRIADI, Drs. Syafwandi, M.Sn, San Ahdi, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Industry lime operating in padang panjang city has header after the long since the days of dutch colonial until now.Development sectors of mining in processing natural resources had long been issued by the city government padangpanjang as one of the strategy and wisdom important to encourage the growth of the local economy. During this industry lime the long maintained individually, by the use of private funds by businessmen lime and lack of the direction of the government.The pattern by mining, the process of combustion, in the manner of a promotion packaging and marketing still conventional.From this background, designer interested to make a design of video feature documentary mine limestone Bukit Tui efforts inform industry limestone who craves direction and cooperation government.Kata Kunci : Batu Kapur, Pemerintah Padang Panjang, video Feature dokumenter